Olahraga dan Identitas: Analisis Filsafat Jean-Paul Sartre - Muhammad Fadillah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss sport and the identity analysis philosophy of Jean-Paul Sartre. This study uses a qualitative approach by applying a descriptive-philosophical method. The formal object of this research is the philosophical theory of Jean-Paul Sartre, while the material object is sport and identity. The results and discussion in this study indicate that in the perspective of Sartre's philosophy, individual freedom is a central concept. Humans are born without a predetermined essence or purpose, and so have absolute freedom to determine the meaning and direction of their lives. A person has the freedom to choose to exercise or not exercise, and that choice reflects personal will and values. In choosing a particular sport, one takes full responsibility for that choice and must face the consequences. This study concludes that sport is an important vehicle in forming individual identity, which is based on the choices, actions, freedoms, and interactions that occur within it.